The British booksellers : a novel of the Forgotten Blitz - Cambron, Kristy (Thomas Nelson, 2024)
"Based on real accounts of Britain's Land Girls and the Forgotten Blitz, The British Booksellers highlights the courageous choices we must make to live, love, and--in the face of all that tests us--fight for what matters most"--